Treatment gap, help-seeking, stigma and magnitude of alcohol use disorder in rural Ethiopia - Selamawit Zewdu; Charlotte Hanlon; Abebaw Fekadu; Girmay Medhin; Solomon Teferra (BMC, 2019)
Abstract Background Although alcohol use disorders contribute a high proportion of population disease burden, the treatment gap is large, especially in low- and middle-income countries. To narrow this gap, contextually relevant evidence is needed to inform service development in low- and middle-income country settings. The aim of this study was to assess the magnitude of the treatment gap for alcohol use disorder, help-seeking behavior, stigma and barriers to care among people with alcohol use disorder in rural Ethiopia. Methods A cross-sectional, house-to-house survey was conducted in Sodo district, south Ethiopia. A sample of 1500 adults was selected using simple random sampling from a census of households and screened for alcohol use disorder using the alcohol use disorders identification tool (AUDIT). Help-seeking, barriers to care and internalized stigma were investigated among people with moderately severe alcohol use disorder (AUDIT score ≥ 16). Poisson regression with robust variance was used to examine factors associated with alcohol use disorder. Results The prevalence of alcohol use disorder (AUDIT ≥8) in the past 12 months was 13.9% (25.8% in men and 2.4% in women, p-value < 0.001). People with alcohol use disorder had increased disability (adjusted prevalence ratio (aPR) 1.03, 95% confidence interval (CI) 1.01, 1.03) and higher depressive symptom scores (aPR 1.02, 95% CI 1.01, 1.04). The treatment gap was very wide, about 87.0% (only 13% sought help) of participants with an AUDIT score ≥ 16 had never sought help for their alcohol problems and 70.0% reported high internalized stigma. Major barriers to seeking help were wanted to handle the problem on their own, believing that it would get better by itself and being unsure about where to go. Conclusions Although alcohol use disorders are common problems in Ethiopian community, the unmet need for treatment is substantial. An integrated care approach has the potential to address this need, but stigma and low awareness may be major barriers to help-seeking. Interventions to reduce stigma and enhance community awareness are recommended.